Global land drought hubs confounded by teleconnection hotspots in equatorial oceans - Tejasvi Chauhan; Vikram Chandel; Subimal Ghosh (npj Climate and Atmospheric Science, 2024)
Abstract Emerging data-driven techniques, such as Complex Networks (CNs), can identify spatial linkages between droughts on a global scale and can improve early warning systems. Recent studies used CNs to identify hotspots of global drought teleconnections as land drought hubs; however, these studies excluded the ocean regions in CN, an oversight that can upend the insights gained thus far. Here, using a comprehensive global CN analysis on drought onsets, we show that oceanic regions harbor significantly larger drought hubs than land regions. The Indo-Pacific Warm pool (IPWP) in the Maritime continent emerges as the most significant drought hub having the farthest teleconnections. We show that IPWP, together with a few sub-tropical land and ocean regions, exhibit a ‘rich club phenomenon’ in CN. Further, using a causal network learning algorithm, we demonstrate the confounding role of oceans in modulating drought onsets on land regions. Our study reveals insights on the spatiotemporal linkages of global drought onsets and highlights the role of oceans in driving global drought teleconnections and modulation of land drought hubs.